Optimal Depreciation Strategies for Income Tax Purposes - Schoomer, B. Alva (Management Science, 1966)
Among the items on a corporate income statement, depreciation and amortization are unique in that while they are legitimate expenses, and therefore deductible for tax purposes, they are non-cash items. Thus, the tax savings which result from reporting depreciation may be retained by the company for investment. If the funds thus generated can be invested profitably, a substantial increase in corporate profitability can result. Typically, this component of the total cash flow of an industrial corporation is two or three times as large as retained corporate earnings. A number of methods for computing depreciation allowances are permitted by law. In addition, switching from one method to another is possible under certain circumstances. The particular method of depreciation which is optimal under a particular set of conditions depends in part upon, the rate of return which the invested funds can yield. It is the purpose of this paper to derive decision rules which select from among the various depreciation alternatives that method which is optimal in a given situation.